Development and application of a portable instrument for drugs analysis in pharmaceutical preparations - Ribeiro, Paulo Roberto da Silva; Pezza, Helena Redigolo [UNESP]; Pezz, Leonardo [UNESP]; Lima, Liliane Spazzapam [UNESP]; Tubino, Matthieu (FapUNIFESP (SciELO), 2015)
This article describes the application and performance of an inexpensive, simple and portable device for colorimetric quantitative determination of drugs in pharmaceutical preparations. The sensor is a light detector resistor (LDR) incorporated into a black PTFE cell and coupled to a low-cost multimeter (Ohmmeter). Quantitative studies were performed with captopril/p-chloranil/H2O2 and methyldopa/ ammonium molybdate systems. Calibration curves were obtained by plotting the electrical resistance of the LDR against the concentration of the colored species in the ranges 1.84 x 10-4 to 1.29 x 10-3 mol L-1 and 5.04 x 10-4 to 2.52 x 10-3 mol L-1 for captopril/p-chloranil/H2O2 and methyldopa/ammonium molybdate systems, respectively, exhibiting good coefficients of determination. Statistical analysis of the results obtained showed no significant difference between the proposed methodologies and the official reported methods, as evidenced by the t-test and variance ratio at a 95% confidence level. The results of this study demonstrate the applicability of the instrument for simple, accurate, precise, fast, in situ and low-cost colorimetric analysis of drugs in pharmaceutical products.
Keywords: Drugs/ quantitative analysis; Drugs/dosage; Instrumentation/drugs dosage; Optical sensor/application/colorimetric analysis; Pharmaceutical formulations/quality control